ROTAVÍRUS DO GRUPO A EM REBANHOS BOVINOS LEITEIROS DA REGIÃO NORDESTE DO ESTADO DE SÃO PAULO - Buzinaro, M. Da G. [UNESP] (2024)
A study was realized in order to determine the occurrence of rotavirus infection among dairy herds from northern region of São Paulo State. Fecal samples from 576 calves, between 1 to 45 days old, were obtained from 63 dairy herds and were analysed by polyacrylamide gel electrophoresis (PAGE). From these samples, 222 belonged to diarrheic animals and 354 to healthy calves. The use of PAGE detected 4.9% (28/576) of positive samples of which 9.9% (22/222) and 1.7% (6/354) belonged to diarrheic and healthy animals, respectively. All positive samples were analysed by enzyme-linked immunosorbent assay (kit-EIARA/Fiocruz) and were classified as rotavirus group A. The analysis of genomic profiles revealed a high diversity with seven distinct electropherotypes.